Country-of-origin (COO) effects in the promotion of functional ingredients and functional foods. Issue 5 (October 2015) - Dobrenova, Fanny V.; Grabner-Kräuter, Sonja; Terlutter, Ralf
Abstract: This paper addresses the research gap concerning country-of-origin (COO) effects in the context of functional foods and functional ingredients. The effectiveness of COO-positioning as an alternative managerial strategy for promoting functional foods with a COO-appeal is examined. An online survey has been administered to young consumers from thirteen European countries. COO-effects on consumers' health evaluations about the functional ingredient L. Casei Shirota and purchase intentions related to hypothetical Shirota-fortified products have been tested. A positive main effect of COO-associations related to Japanese functional foods on both ingredient healthiness perception and purchase intention occurs. The moderating COO-effect intensifies the favorable impact of ingredient healthiness perception on purchase intention. An indirect effect of ingredient familiarity on purchase intention via ingredient healthiness perception is observed at high and moderate COO-levels, while at low COO-levels no mediation takes place.